Ojakly: A Late Bronze Age mobile pastoralist site in the Murghab Region, Turkmenistan. (February 2014) - Rouse, Lynne M.; Cerasetti, Barbara
Abstract : Excavations at Ojakly (site 1744) in the Murghab alluvial fan in Turkmenistan mark the first systematic collection of archaeological materials related to Bronze Age mobile pastoralists in the region, and the earliest evidence to date of their occupation patterns, subsistence practices, and ceramic production activities. Because the appearance of mobile pastoral groups in the Murghab during the Late Bronze Age (ca. 1950–1500b.c. ) is traditionally associated with significant changes in regional sociopolitical structures, these data are important for establishing local strategies of and the relationship between sedentary agricultural and mobile pastoral populations. Here, we present ceramic, faunal, archaeobotanical, and lithic data that force us to reconsider the traditional sedentary-mobile dichotomy. Specifically, we find that while the subsistence economies are distinct at urban and non-urban sites, the ceramic production and trade interactions are significantly intertwined and more complex than previously acknowledged for this time period. Additionally, the presence of a ceramic kiln at Ojakly (Turkmen for "place with kiln") containing unfired ceramics of a type typically associated with sedentary farmers in the Bronze Age Murghab suggests the transfer of technical knowledge between groups who nevertheless maintained distinct material cultural identities. Ojakly provides important new data about coexisting economies in the Late Bronze Age Murghab that can productively unsettle traditional notions of dominance, control, and polarization in sedentary-mobile interactions.